ترکی کےنظام تعلیم کاارتقائی سفراورپاکستان کے نظام تعلیم سے تقابلی جائزہ ،ایک تحقیقی مطالعہ: The evolutionary journey of The Turkish education system, and a comparative study with Pakistan's education system, a research study. (Khairulummah, 2022)
Turkey is one of the most important Muslim states in modern era. Turkey is one of the Muslim countries where the literacy rate is much better than other Muslim countries. If it is said that Turkey can be an example for modern Muslim countries, this statement would not be an exaggeration. According to the Countrymeters report, Turkey's literacy rate in 2022 was 95.12%, while the literacy rate for 15 to 24 year-olds was 99.25%, this suggests that Turkey is one of the most developed countries in the world.In this article we analysis  the Turkish education system and try to find out how Turkey achieved these victories in the field of education. After analyzing the Turkish education system, this system has been compared with the education system of Pakistan, and the fundamental flaws in Pakistan's education system have been identified in the context of Turkey's education system , and the steps to be taken for their best solution have also been discussed.
Keywords: Turkey،; important،; modern،; countries،; exaggeration